Nutritional Constituents, Phytochemical Analysis and Biological Evaluation of Momordica charantia (Bitter Gourd) Leaf and Stem Ethanol Extracts - Anomi, Etudaiye; Ndukaire, Victoria; Afolayan, Michael (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Momordica charantia L. (Cucurbitaceae), locally known as Ejirin or bitter gourd, is widely used in Nigerian traditional medicine for its purported health-promoting properties. This study aimed to evaluate the proximate, nutritional, phytochemical profile, antioxidant and antimicrobial efficacy of the leaves and stems of M. charantia. Ethanolic extracts were prepared and subjected to standard analytical protocols. Proximate analysis revealed that the leaves contained 18.22% ash, 39.43% crude fiber, 4.02% crude protein, and a metabolizable energy value of 96.52 kJ, indicating significant nutritional potential. In contrast, the stems exhibited an exceptionally high fiber content (77.65%) but a negative calculated energy value (?39.44 kJ). Phytochemical screening confirmed the presence of alkaloids, flavonoids, tannins, resins, and saponins in the leaves, while the stem contained alkaloids, tannins, steroids, triterpenoids, and phenols. The leaf extract demonstrated potent antioxidant activity, with 74.96% DPPH radical scavenging at 2 mg/mL. Antimicrobial assays showed that the leaf extract was effective against Staphylococcus aureus, Escherichia coli, and Candida krusei, while the stem extract exhibited broad-spectrum activity against both Gram-positive and Gram-negative bacteria. These findings provide a scientific basis for the traditional use of M. charantia leaves as a wellness supplement and highlight the stems as a potential source of dietary fiber. Keywords: Momordica charantia, bitter gourd, phytochemicals, antioxidant activity, antimicrobial activity